2020
DOI: 10.1186/s12885-020-07146-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern and prognosis of metastatic lymph nodes in cervical posterior to level V in nasopharyngeal carcinoma patients

Abstract: Background: Lymph node metastasis in the cervical region posterior to level V (PLV) can occurs in patients with nasopharyngeal carcinoma (NPC), but the significance of lymph node metastasis in this region and the delineation of the radiotherapy target area have not been reported. We aimed to explore the distribution pattern and prognosis of metastatic lymph nodes in the PLV region in patients with NPC. Methods: We retrospectively studied 605 cases of NPC diagnosed by pathological detection from December 2011 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…The involved groups of lymph nodes are also important to note as seen in a study by Chaoyang Jiang et al, which showed that metastasis to lymph node posterior to level V had independent prognostic factor for Distant metastasis free survival. 21 The biopsy obtained by nasal endoscopy in our study showed that non-keratinizing undifferentiated carcinoma (33/34) was seen in almost all the cases. This is the major histological subtype seen in endemic regions.…”
Section: Discussionsupporting
confidence: 46%
“…The involved groups of lymph nodes are also important to note as seen in a study by Chaoyang Jiang et al, which showed that metastasis to lymph node posterior to level V had independent prognostic factor for Distant metastasis free survival. 21 The biopsy obtained by nasal endoscopy in our study showed that non-keratinizing undifferentiated carcinoma (33/34) was seen in almost all the cases. This is the major histological subtype seen in endemic regions.…”
Section: Discussionsupporting
confidence: 46%
“… 15 The metastatic status of the CLNs is an essential indicator in the cN staging of NPC and has crucial implications for the target volume delineation and planning radiotherapy. 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
“… 2 The metastatic status of the CLNs is an essential indicator in the staging of NPC and has crucial implications for the formulation of treatment plans, such as induction chemotherapy and target volume delineation. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the PLV region is often overlooked. We have reported the correlations between the PLV region and other NNL, the distribution of metastatic lymph nodes in the PLV region in our previous studies 9 , 10 , but what is the boundary of PLV region and how to delineate it is still unclear.
Figure 1 The yellow line represents trapezius, the red line represents levator scapulae, the green line presents the serratus anterior muscle, and the purple line presents the supraspinatus.
…”
Section: Introductionmentioning
confidence: 96%
“…1 ). Several studies have reported the metastasis rate of PLV region is 1.3–4.9% 7 9 . Unfortunately, the PLV region is often overlooked.…”
Section: Introductionmentioning
confidence: 99%